2018
DOI: 10.21307/ane-2018-025
|View full text |Cite
|
Sign up to set email alerts
|

The use of MR-less MNI based neuronavigation for 10 Hz rTMS depression therapy: electrophysiological and clinical implications

Abstract: Repetitive transcranial magnetic stimulation (rTMS) is a popular and effective treatment for drug resistant depression. However, there is considerable variability in clinical outcomes, in previous studies and between patients. Because of high requirements for the use of fMRI based neuronavigation, many practitioners of rTMS still choose to use a standard 5 cm rule for rTMS coil placement which leads to large variations in which brain regions are being stimulated. We decided to test the possibilities of a MNI b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 56 publications
(91 reference statements)
0
13
0
Order By: Relevance
“…The need for this precision in clinical applications must be balanced against whether the use is feasible in any particular setting, and whether the application shows evidence that failure to use neuronavigation would lead to inadequate outcomes. Settings without access to an MRI could use a template brain that is adapted to individuals ; however, without a dedicated, trained staff, the technique is unfeasible. In the case of rTMS for chronic pain, the brain target with the most evidence for effectiveness is M1 contralateral to the side of pain .…”
Section: Technical Issuesmentioning
confidence: 99%
“…The need for this precision in clinical applications must be balanced against whether the use is feasible in any particular setting, and whether the application shows evidence that failure to use neuronavigation would lead to inadequate outcomes. Settings without access to an MRI could use a template brain that is adapted to individuals ; however, without a dedicated, trained staff, the technique is unfeasible. In the case of rTMS for chronic pain, the brain target with the most evidence for effectiveness is M1 contralateral to the side of pain .…”
Section: Technical Issuesmentioning
confidence: 99%
“…Figure 3 presents power grand averages and standard error of the mean bars across all patients and EEG recording sessions (i.e., pre-and posttreatment). For each EEG sensor, peaks in activity consistently appear in delta/theta (1-6 Hz), alpha (7-14 Hz), and beta range (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). As such, these bands defined the frequency boundaries for all further analyses.…”
Section: Ptsd and Mdd Symptoms Improved After Rtmsmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted March 16, 2023. ; https://doi.org/10.1101/2023.03.11.23286902 doi: medRxiv preprint averaged local band power [16,17,18], event-related power and coherence [19,20], and for varied measures of time-domain signal complexity [21]. Recent studies applying machine learning showed that rTMS-induced changes in resting-state EEG coherences were predictive of clinical response in comorbid PTSD/MDD and able to distinguish active, sham, pre-treatment, and post-treatment groups [22,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term paroxetine therapy was linked to an increase in Beta1 power in patients with major depression, according to post-medication EEG research, which suggested that Beta1 power was regulated by mood changes [40]. rTMS administered at 1 Hz over the right dorsolateral prefrontal lobe in depressed patients resulted in a marked increase in Beta oscillation [41]. An earlier investigation revealed that 1Hz-rTMS over the right DLPFC for treating depression led to a notable increase in Beta power.…”
Section: Analysis Of Abnormal Power Spectrummentioning
confidence: 99%